Cold‐pool formation in a narrow valley. (19th June 2013) - Vosper, S. B.; Hughes, J. K.; Lock, A. P.; Sheridan, P. F.; Ross, A. N.; Jemmett‐Smith, B.; Brown, A. R.
Abstract A numerical model simulation of the formation of a cold pool within a narrow valley during a clear calm night is presented. The results are compared with measurements made during the COLd air Pooling EXperiment (COLPEX). It is demonstrated that the model provides a realistic simulation of the observed cold pool. The cold pool begins to form approximately 1.5 hours before sunset, when the near‐surface air within the valley starts to cool more rapidly than the air on the surrounding hills. The model potential temperature budget is used to determine which physical processes are most important for the evolution of the cold pool. The results show that sheltering provided by the valley causes a turbulent heat ﬂux divergence over the lowest 5 m above the valley ﬂoor, which is large compared with the other terms in the budget. This causes relatively rapid cooling of the air adjacent to the ground. On the surrounding hills the turbulent heat ﬂux divergence is larger than in the valley, but the enhanced cooling this provides is approximately balanced by an almost equally large warming tendency from advection. The net eﬀect of these two terms is small compared with that in the valley and therefore the cooling rate is smaller. Above 5 m, the cooling in the valley is dominated by local transport of cold air away from the surface into the interior valley atmosphere.